WACANA PERKEMBANGAN PENDIDIKAN ISLAM DI INDONESIA: PENDEKATAN HISTORIS DAN SOSIOLOGIS - Edi Kurniawan Farid (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2017)
This paper tries to explain the developments of thought associated with Islamic Education in Indonesia and it’s dynamics that occurred before the period of independence, post-independence until today. What the writer describes here be presented with a historical-sociological approach, also explain the discourses that developed in it. In general, Islamic education in Indonesia before independence faced several phases, those can be exposed in three major processes. First, the process of transmission and internalization of Islamic values and Islamic Education. Second, the process of Islamic Education as a self-defense of colonialism. Third, the process of transition to the renewal of Islamic Education. Furthermore the phase of post-independence, Islamic Education in Indonesia is still in the phase of ideal model searching process in Islamic Education. The search for this ideal model will continue to response and answer the developments and the challenges of the modern world that required by mastering science and technology. The efforts that have been passed are first, the integration of Islamic Education in the national education system. Second, the rise of excellent Islamic Schools. Thirdly, the most recently is the back-to-pesantren effort, that seeking the pesantren system as a reference model of Islamic Education considering the pesantren as an indegeneous education form in Nusantara whose still existed since long ago